2023
DOI: 10.32942/x2n31x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fifteen years of extensive and inadvertent elasmobranch trade in Brazil detected by DNA tools

Marcela Alvarenga,
Ingrid Bunholi,
Gustavo Brito
et al.

Abstract: The trade of elasmobranchs (sharks and rays) in Brazil raises significant concerns due to the country's rich endemic biodiversity. The present study explores the use of DNA-based tools to monitor the Brazilian elasmobranch trade, focusing on their role in identifying processed products and supporting conservation efforts. A systematic search of literature was carried out and included 35 peer-reviewed articles published between 2008 and 2023. We observed a shift in research focus since 2015 from the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The study and resource building for DD and NT species should be a conservation priority, since the DD status may represent an already threatened species without human knowledge, whilst NT represents species that are close to endangered categories. It has been shown that shark and ray species that were previously classified as DD and NT have now become threatened [58]. Another conservation gap that many Latin American fisheries resources face is the lack of assessment of species conservation status.…”
Section: Molecular Resources For Fisheries Managementmentioning
confidence: 99%
“…The study and resource building for DD and NT species should be a conservation priority, since the DD status may represent an already threatened species without human knowledge, whilst NT represents species that are close to endangered categories. It has been shown that shark and ray species that were previously classified as DD and NT have now become threatened [58]. Another conservation gap that many Latin American fisheries resources face is the lack of assessment of species conservation status.…”
Section: Molecular Resources For Fisheries Managementmentioning
confidence: 99%